Trzy kroki w stronę obrazów. Pierre Bonnard i percepcyjne opóźnienie. - Kiepuszewski, Łukasz (Artium Quaestiones, 2018)
The essay is an analysis of three interpretations of Pierre Bonnard’s paintings offered by Jean Clair, John Elderfield, and Yves-Alain Bois. Their approaches are crucial in the context of the revaluation Bonnard’s works and his place in the history of modern painting, which has been continuing since the 1980s. Today’s scholars have been interested mostly in his late works from 1920-1947. At that time the artist created a multidimensional pictorial synthesis which addressed the most advanced dilemmas which appeared in the first half of the 20th century. The critical opinions analyzed in the essay, referring to physiology and the psychology of perception, the cognitive conditions of visual perception, and specific philosophical traditions, stem from individual visual experience and demonstrate significant tensions. Taking the painting as a starting point triggers differences in interpretation not just at the level of theoretical discourse, but in respect to visualization itself. Bonnard’s works significantly program the process of visual perception – grasping the changing rhythm of relation between the center and periphery and moving toward fixations scattered in the visual field. The specific composition of paintings makes the spectator deconcentrate; it can be grasped in an act of perception which extends in time. Such “delay” of perception means that Bonnard’s paintings are a challenge to the gestalt psychology which prevails in the analytical practice of art history. The unique quality of Bonnard’s works, based on the coexistence of the rhythms of organization and disorder,shows no superior coherence of the gestalt. They establish an “inconclusive” relation between the part and the whole, which results in continuing deference and delay of the integration of motifs and elements of the pictorial field. The discussed episode in Bonnard’s art’s reception confirms a belief that “he is not a painter for those in a hurry. The phenomenon of the perceptive delay seems to be significantly connected with the delay in discovering such qualities by art historians.